Legal Protection for Islamic Boarding School Workers: Case Study of Overtime Policy Implementation at Al-Ma’tuq Islamic Boarding School Based on Law No. 13 of 2003 - Rinaldi, Andhika; Putri, R. Eriska Ginalita Dwi (Dinasti Research, 2025)
In the context of employment, legal protection is essential to ensure workers' rights are met, including equal treatment and opportunity without discrimination. Based on Law Number 13 of 2003 concerning Manpower, every worker is entitled to fair remuneration, especially for those who work beyond the stipulated working hours. The research method used is a qualitative approach with descriptive analysis, which involves interviews and direct observation at the Al-Ma'tuq Islamic Boarding School. The results of the study show that even though there is an overtime policy, its implementation is not fully in accordance with the applicable legal provisions. This study recommends the need for policy revisions and improved communication between management and workers to create a fairer and more transparent work environment.